The Effect of Word of Mouth (WOM) on Purchasing Decision of Region Exclusive Fabric of West Nusa Tenggara Province (Case Study on Sasambo Fabric in Bima City) - Sri Ernawati; Muhajirin Muhajirin; Ismunandar Ismunandar (STKIP Singkawang, 2018)
Word of mouth (WOM) become an important part in marketing studies considering that communication in Word of mouth (WOM) is able to influence the consumer. Word of mouth (WOM) is capable of spreading rapidly when the individual who is spreading it also has a wide network. This study aims to (1) to find out and analyze the positive and significant effect of Word of Mouth (WOM) on purchasing decision of region-exclusive fabric of West Nusa Tenggara Province (case study on Sasambo fabric in Bima City), (2) to give an input of thought to sasambo fabric manufacturer in Bima Town to implement the marketing strategy that does not rely on high cost but what is required is loyal consumer, so that the quality of sasambo fabric is must be upgraded and has more variety in motif. The research is conducted in Bima town for 2 months from Mei to June 2018. The population of this research is all of the people in Bima who bought and used Sasambo cloth with a number of samples are 96 people and technique of sampling is purposive sampling. The technique of Data analysis used is a simple linear regression analysis by using the equation, i.e: Y = a +bx. The result variable statistic test of WOM achievement point in the amount of 17.541 with table point in the amount of 1,985 (17.541 ˃1,985), then, so Word of Mouth (WOM) has a positive and significant effect on purchasing decision of region-exclusive fabric of West Nusa Tenggara province (Case Study on Sasambo Fabric in Bima City).